99mTechnetium Sestamibi-123Iodine Scintigraphy Is More Accurate Than 99mTechnetium Sestamibi Alone before Surgery for Primary Hyperparathyroidism. (1st February 2015) - Ryhänen, Eeva M.; Schildt, Jukka; Heiskanen, Ilkka; Väisänen, Mika; Ahonen, Aapo; Löyttyniemi, Eliisa; Schalin-Jäntti, Camilla; Välimäki, Matti J.
Abstract : Objectives . Studies comparing outcome of single-T 99 m c-methoxyisobutylisonitrile (T 99 m c-sestamibi) and dual-tracerT 99 m c-sestamibi scintigraphy in combination with 123 I before primary surgery of primary hyperparathyroidism (PHPT) are scarce. Methods . We comparedT 99 m c-sestamibi/ 123 I andT 99 m c-sestamibi in a single-centre retrospective series of 269 PHPT patients. The results were related to laboratory, surgical and histological findings. Results .T 99 m c-sestamibi/ 123 I andT 99 m c-sestamibi were positive in 206 (76.6%) and 111 (41.3%) of 269 patients, respectively ( P < 0.001). Accuracies forT 99 m c-sestamibi/ 123 I andT 99 m c-sestamibi were 63.4% and 34.9%, respectively (96% CI, P < 0.001). Prevalence of multiglandular disease was 15.2%. In multiglandular disease, T 99 m c-sestamibi/ 123 I andT 99 m c-sestamibi revealed 43.8 and 22.1% of pathological glands, respectively ( P < 0.001). Cure rate was similar for patients with (191/206; 92.7%) and without (59 of 63; 93.7%) a positiveT 99 m c-sestamibi/ 123 I finding. Duration of targeted surgery (one or two quadrants) was 21 and 15 minutes shorter than bilateral neck exploration, respectively (both P < 0.001). Higher serum calcium ( P = 0.014) and PTH ( P = 0.055) concentrations and larger tumours ( P < 0.001) characterized the 206 patients with a positive preoperative scan who were cured by removal of a single adenoma. Conclusions .T 99 m c-sestamibi/ 123 I scintigraphy is more accurate thanT 99 m c-sestamibi before surgery of PHPT. However, outcome of surgery is not determined by scintigraphy alone.